2019
DOI: 10.1016/j.omtn.2019.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Microglia Attenuate Photoreceptor Injury and Neovascularization in an Animal Model of Retinopathy of Prematurity

Abstract: The role of microglia in the pathophysiology of ischemic retinal diseases has been studied extensively. Exosomes from microglial cells exert protective effects during several nervous system diseases, but their roles in hypoxia-induced retinopathy remain unclear. In our study, exosomes derived from microglial cells were injected into the vitreous body of mice with oxygen-induced retinopathy (OIR). Results showed that exosome-treated OIR mice exhibited smaller avascular areas and fewer neovascular tufts in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…Nonetheless, in the early stages of the disease, EVs can also exhibit protective effects, preventing the rapid progression of the retinal damage. For example, in vitro and in vivo studies have demonstrated that EVs derived from microglial cells were able to inhibit hypoxia-induced photoreceptor apoptosis, thus preventing neovascularization and alleviating visual injury [76].…”
Section: Crosstalk Between Endothelial Cells and Other Retinal Cells mentioning
confidence: 99%
“…Nonetheless, in the early stages of the disease, EVs can also exhibit protective effects, preventing the rapid progression of the retinal damage. For example, in vitro and in vivo studies have demonstrated that EVs derived from microglial cells were able to inhibit hypoxia-induced photoreceptor apoptosis, thus preventing neovascularization and alleviating visual injury [76].…”
Section: Crosstalk Between Endothelial Cells and Other Retinal Cells mentioning
confidence: 99%
“…As CCL2 has been implicated as a key chemokine in the pathogenesis of multiple retinal degenerative diseases (Newman, Gallo et al 2012, Rutar, Natoli et al 2012, Zuzic, Rojo Arias et al 2019, and is a known target of miR-124-3p (Zuzic, Rojo Arias et al 2019); exosome-based therapies that replenish retinal levels of this miRNA may prove efficacious as a possible therapeutic, as evidenced in other works (Chu-Tan, ). In addition, exosomes derived from microglial cells and injected into the vitreous of mice subjected to oxygen-induced retinopathy showed protective effects, reducing avascular regions in the retina, VEGF expression, and photoreceptor apoptosis, compared to controls (Xu, Wu et al 2019). It was hypothesized by these authors that exosomal-miR-24-3p mediated this protection against hypoxia-induced cell death (Xu, Wu et al 2019).…”
Section: Exosomes As Mediators Of Phototransductionmentioning
confidence: 99%
“…In addition, exosomes derived from microglial cells and injected into the vitreous of mice subjected to oxygen-induced retinopathy showed protective effects, reducing avascular regions in the retina, VEGF expression, and photoreceptor apoptosis, compared to controls (Xu, Wu et al 2019). It was hypothesized by these authors that exosomal-miR-24-3p mediated this protection against hypoxia-induced cell death (Xu, Wu et al 2019).…”
Section: Exosomes As Mediators Of Phototransductionmentioning
confidence: 99%
“…Further evidence that EV therapy might be beneficial for retinal conditions derives from a recent study that employed microglial-derived exosomes [44]. The rationale behind the use of these exosomes in ROP is that microglial cells play a role in the innate immune response and normal vascular development of the retina [45,46].…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%
“…The rationale behind the use of these exosomes in ROP is that microglial cells play a role in the innate immune response and normal vascular development of the retina [45,46]. Using an in vivo mouse model of oxygen-induced retinopathy, Xu et al showed that intravitreal administration of microglial-derived exosomes limited the central avascular area, reduced the area of retinal neovascularization, and decreased the expression of hypoxia-induced VEGF, which is considered the most important factor involved in the retinal neovascularization process [44]. Moreover, electroretinography data established better visual function in microglia-derived exosome-treated retinas [44].…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%